Microcounselling Supervision: An Innovative Integrated Supervision Model - Russell-Chapin, Lori A.; Ivey, Allen E. (Canadian Journal of Counselling and Psychotherapy, 2007)
This article introduces a new integrated model of counselling supervision entitled the Microcounselling Supervision Model (MSM). This type of supervision is designed for supervisors and supervisees who favor eclecticism and work from multiple theoretical orientations. MSM successfully combines skills from various theories and supervision models by reviewing basic counselling skills, classifying those same skills and processing needed supervisory information gleaned from the interviewing session. The Counselling Interview Rating Form (CIRF), an integral instrument used in this model, is illustrated using examples from a case study.